Using the inverse trig functions, find the measure of the missing angle.​
Using the inverse trig functions, find the measure of the - 1

Answers

Answer 1
Answer:

Answer:

? ≈ 24°

Step-by-step explanation:

using the sine ratio in the right triangle

sin? = (opposite)/(hypotenuse) = (11)/(27) , then

? = sin^(-1) ( (11)/(27) ) ≈ 24° ( to the nearest degree )


Related Questions

Jose has $178.74 in his checking account. He wrote checks for $36.52, $18.92, and $25.93. He also deposited $300.00, $100.00, and $205.16. What is the final balance in Bob's checking account?V
Find the slope of each line.
A ladder of length 2x+1 feet is positioned against a wall such that bottom is x-1 feet away from a wall. The distance between the floor and top of the ladder is 2x. Assume that a right angle is formed by wall and the floor.
A certain book is for sale in both Belize and Brazil. In Belize, it sells for 80.39 Belize dollars. In Brazil, it sells for 63.65 Brazilian reals. The exchange rate of US dollars to Belize dollars is 1:1.9246, and the exchange rate of US dollars to Brazilian reals is 1:1.7880. When converted into US dollars, which country sells the book at a more expensive price, and how much more expensive is it? Round all currency values to two decimal places.
$800 deposited at 9% for 9 months, what is the simple interest and total amount?

Given ƒ(x) = 3x - 1 and g(x)= -x + 6, find ƒ(-2) + g(5).
-6
6
8

Answers

This should be the answer


Given ƒ(x) = 3x - 1 and g(x)= -x + 6, find ƒ(-2) + g(5).


f(-2) = 3(-2) =-6 -1 = -7

g(5) = -(5) = -5 +6= 1


-7+1= -6

Answer: -6

 f(x) = 3x - 1
g(x) = -x + 6

f(2) + g(5) = (3(2) - 1) + (-(5) + 6)
f(2) + g(5) = (6 - 1) + (-5 + 6)
f(2) + g(5) = 5 + 1
f(2) + g(5) = 6

The answer is C.

For the function y=-3+4cos (5pi/6 (x+4)), what is the minimum value

Answers

interval <-1;1>, which means that this function can take values from interval <-7;-1>. The minimum value is -7.

the min of cos (5pi/6(x+4) = -1

so the min of 4cos 5pi/6(x+4 = -4

so the min of -3 + 4 cos 5pi/6(x+4 = -7

How do you find the minimum value?

If the quadratic equation has a positive term, it also has a minimum value. This minimum can be found by graphing the function or by using one of the two equations. If you have an equation of the form y = ax ^ 2 + bx + c, you can use the equation min = c --b ^ 2 / 4a to find the minimum value.

Rearrange the function using basic algebraic rules and solve the value of x when the derivative is zero. This solution provides the x-coordinates of the vertices of the function where the maximum or minimum values ​​occur. Convert to the original function and solve to find the minimum or maximum value.

Learn more about the function at

brainly.com/question/10439235

#SPJ2

Answer:

-7

Step-by-step explanation:

A P E X

HELP W/ ACT PREP QUESTION PLEASE I NEED TO DO WELL AND NEED YOUR HELP!!: At a school picnic, 1 junior and 1 senior will be selected to lead the activities. If there are 125 juniors and 100 seniors at the picnic, how many different 2-person combinations of 1 junior and 1 senior are possible???A. 25
B. 100
C. 125
D. 225
E. 12,500

Answers

the answer is e  you multiply 125 by 100

Simplify 20 + (2 + r).

Answers

the answer is 22+r
:]

if julie ran 3.6 miles from home to the gym and then walked 0.7 miles to the store she then ran from the store home if her total distance covered after she returned from the store was 7.2 miles how far is it from the store to her home? write and simplify and expression that would represent the distance she covered.

Answers

So,

Home ---- gym = 3.6 mi.
gym   ---- store = .7 mi.
store ----- home = x

3.6 + .7 + x = 7.2 mi.

Collect Like Terms

4.3 + x = 7.2

Subtract 4.3 from both sides
x = 2.9

The distance from the store to her home is 2.9 miles.

One number is 4 less than 3 times a second number. If 3 more than two times the first number is decreased by two times the second, the result is 11. What are both numbers?

Answers

The 1st number is x and the 2nd number is y:

x = 3y-4
3 + 2x - 2y = 11

The first equation says that x is equal to "3y - 4", so you can plug in "3y - 4" for x in the second equation:

3 + 2(3y - 4) - 2y = 11
3 + 6y - 8 - 2y = 11
-5 + 4y = 11
4y = 16
y = 4

Now that you have y, you can plug it into the 1st equation to get x:

x = 3y - 4
x = 3(4) - 4
x = 12 - 4
x = 8

So, the 1st number is 8 and the 2nd number is 4.